Application of Multi-agent and Genetic Algorithm in Network Reconfiguration of Ship Power System - Wang, Zheng; Xia, Li; Wang, Yongji (Elektronika ir Elektrotechnika, 2012)
Network reconfiguration of ship power system may be abstracted as a typical non-linear discrete optimization problem featuring multi-target and multi-constraint. According to the characteristics of ship power system, simplified network model and reconfiguration mathematical model of ship power system are established. A multi-agent and genetic algorithm is presented. The results of simulation show that multi-agent and genetic algorithm can reconfigure shipboard power system efficiently. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2795